Analyses of the Department of Defense acquisition workforce : update to methods and results through FY 2011 - Gates, Susan M., 1968-; Roth, Elizabeth; Srinivasan, Sinduja; Daugherty, Lindsay (Research report (Rand Corporation), 2013)
The organic defense acquisition workforce consists of military personnel and Department of Defense civilian personnel who provide the management, technical, and business capabilities needed to oversee defense acquisition programs from start to finish. This workforce must itself be managed so that the right numbers of the right personnel are in the right positions at the right time. Since 2006, RAND has been helping develop data-based tools to support analysis of this workforce. This volume updates a 2008 report by documenting revisions to methods, providing descriptive information on the workforce through fiscal year 2011, and providing a user's manual for a model that can help managers project workforce needs through 2021 under different assumptions about the future. The report illustrates the use of the model.